Simultaneous control of stemness and differentiation by the transcription factor Escargot in adult stem cells: How can we tease them apart?. Issue 2 (2nd April 2016) - Loza-Coll, Mariano A.; Jones, D. Leanne
ABSTRACT: The homeostatic turnover of adult organs and their regenerative capacity following injury depend on a careful balance between stem cell self-renewal (to maintain or enlarge the stem cell pool) and differentiation (to replace lost tissue). We have recently characterized the role of the Drosophila Snail family transcription factor escargot ( esg ) in testis cyst stem cells (CySCs) 1, 2 and intestinal stem cells (ISCs). 3, 4 CySCs mutant for esg are not maintained as stem cells, but they remain capable of differentiating normally along the cyst cell lineage. In contrast, esg mutant CySCs that give rise to a closely related lineage, the apical hub cells, cannot maintain hub cell identity. Similarly, Esg maintains stemness of ISCs while regulating the terminal differentiation of progenitor cells into absorptive enterocytes or secretory enteroendocrine cells. Therefore, our findings suggest that Esg may play a conserved and pivotal regulatory role in adult stem cells, controlling both their maintenance and terminal differentiation. Here we propose that this dual regulatory role is due to simultaneous control by Esg of overlapping genetic programs and discuss the exciting challenges and opportunities that lie ahead to explore the underlying mechanisms experimentally.